THE FATTY ACID COMPOSITION OF SEED OILS OF CITRUS SINENSIS VARIETIES: VALENCIA AND SALUSTIANA (Biological Sciences - PJSIR, 2001)
The percentage yield and chemical composition of fixed oil of Citrus sinensis varieties Valencia and Salustiana have been  studied. The percentage  yield  of fi xed  oils  from t he seeds of these two  var i eties  were 40.0 I   and 36.66%respecti vel y. The percentage  fatty acids com position of the respecti ve oils were characterised as C12 (  1 .55, 0.0 ), C ,( 5.04 , 0 0), C ,,( 47 .33, 29 . 1 3), C J 7.50, 4.23) , C,s/ 1 8.40, 26.03) ,C, ,(l 8.39, 37 .51) and C, /0.0, 3.07) 1                                       1                                                18                                                                                              8                                                          8respecti vel y. This chemical composition suggests that the oils, when a vailable i n quan tity can fi nd appl ication bothfor edible or soap maki ng purposes.